"Essential Not Optional": Spiritual Care in Australia during a Pandemic. (April 2021) - Tan, Heather; Holmes, Cheryl; Flynn, Eleanor; Karimi, Leila
This paper focuses on the impact of COVID19 in Australia. Three areas were investigated: professionalism, contrasting hospital and aged care services and "business as usual"? Impact was low overall, the timing being pre-second wave impact. Two areas of weakness were highlighted: depleted spiritual care teams due to standing down non-professional staff and uncertainty about the role of Chaplains in the care of other staff. Further study of second wave impact is recommended.